Of portrayal and perception an analysis of the local news media's portrayal of the Philippine government during the Marawi crisis and how it is reflected on the audience's perception - Ramos, Christine Bettina O. 1996-; Ramos, Ma. Bianca Vanessa D.; San Pascual, Maria Rosel S. (2018)
"In crisis situations, mass media serves as a critical source of information for the public. Aside from this, media also wields influence. According to McNair (2011), the information presented by the media impacts the audience's perception of events and the people who are involved in it. This research analyzed how the local news media's portrayal of government actors involved during the Marawi crisis reflected on the audience's perception of the government's efficacy in handling political crises. To examine media portrayal, the researchers content analyzed TV Patrol's and 24 Oras' news episodes aired from may 23, 2017 until January 31, 2018. The researchers identified the government actors involved, the issues associated with them, and the tone the news media used in portraying them. Meanwhile, a quantitative survey was conducted to measure audience's perception. The researchers assessed the audience's satisfaction with the government's performance, perceived effectiveness of the government's actions, and trust in the government actor's capability to handle similar crises in the future. Although previous studies have confirmed manifestations of media malaise and virtuous circle theories, this research found that there was a significant difference between media portrayal and audience perception."
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Marawi crisis -- Press coverage